A RETROSPECTIVE ANALYSIS OF SELECTIVE HISTOLOGICAL EXAMINATION VERSUS ROUTINE HISTOLOGICAL EXAMINATION AFTER CHOLECYSTECTOMY FOR GALLBLADDER STONES. - Baskey, Shyam Charan; Baski , Babumani; Gupta, Shambhu Prasad (Student’s Journal of Health Research Africa, 2024)
Background The usual histological examination is carried out after the cholecystectomy procedure has been completed to determine whether or not the patient has a malignancy. There is a very low probability that cancer will be discovered during a routine checkup after cholecystectomy. The study aims to investigate the incidence of gall bladder cancer among patients who have had cholecystectomy surgeries. Method A retrospective study was conducted and the data of the patients who underwent cholecystectomy for gallbladder stones were included in this study. The patients in which incidental gall bladder cancer was recorded were compared with the patients with no gall bladder cancer in terms of the morphology of the gall bladder, histopathology of the gall bladder specimen, and other clinical features. The risk factors associated with gall bladder cancer were determined. Results Out of 1198 cases analyzed, 4 patients (0.33%) had IGBC. The average age was 53 years, with malignancy patients averaging 72 years and benign cases 43 years. Among IGBC patients, 3 were female and 1 male, showing a significant correlation with female gender (p < 0.05). Emergency cholecystectomy was performed in 143 cases, with 3 (2.1%) having cancer, compared to 1 in the elective surgery group (p = 0.02). All cancer patients exhibited macroscopic abnormalities like thickened walls, polyps, ulceration, and calcification. The average survival time for IGBC patients was 15 months, with treatments including chemotherapy and radiotherapy. Conclusion Risk factors associated with gall bladder cancer identified in this study include female gender, advanced age, conversion of the surgery, emergency surgery, and macroscopic abnormalities in the gall. Selective histopathology for diagnosis of gall bladder cancer in patients undergoing cholecystectomy is effective and does not compromise the health of the patients. Recommendation Selective histopathology should be preferred over routine histopathological examination after cholecystectomy.